Production of canned meat for children's food in Ukraine - Hashchuk, Oleksandra; Moskaluyk, Oksana; Verba, Natalia (My University, 2018)
The largest assortment of canned food for baby food in the Ukrainian market is represented by the trademark "Hipp" (Austria). This enterprise produces products for infants aged from 4 months to 3 years, including mashed turkey meat, chicken, beef. Trademark "Tema" and "Hame" (Czech Republic) represent approximately the same number of varieties of meat and meat and vegetable mashed potatoes in glass and metal containers of 100 g. Найбільший асортимент консервів для дитячого харчування на українському ринку представлений торговою маркою "Хіпп" (Австрія). Це підприємство випускає продукцію для немовлят у віці від 4 місяців до 3 років, включаючи м'ясо індички, курку, яловичину. Торгова марка "Tema" та "Hame" (Чехія) складають приблизно однакову кількість сортів м'яса та м'яса та овочів пюре в скляних та металевих контейнерах по 100 г.
Keywords: дитяче харчування; baby food; консерви; canned food; м'ясо індички; turkey meat; кафедра технології м’яса і м’ясних продуктів